2020
DOI: 10.1021/acsmaterialslett.0c00133
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Organic Antimony Halide Crystals for X-ray Scintillation

Abstract: Scintillators are utilized for X-ray detection in many important fields ranging from homeland security to health care. Developing low-cost, high-performance scintillation materials to address the issues of existing commercially available ones is of great interest. Recently, organic metal halide hybrids have emerged as highly promising luminescent materials with excellent optical properties and low-temperature solution processability. Herein, we report a zero-dimensional organic metal halide hybrid, (PPN)2SbCl5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
144
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(153 citation statements)
references
References 43 publications
3
144
0
Order By: Relevance
“…The intensity decreased to the background level in 10 ms after the cease of the excitation source, indicating the suitability for high contrast imaging. The excellent performance of X-ray imaging could be attributed to the negligible self-absorption, high PLQE, light yield, and low detection limit of (C 38 H 34 P 2 )MnBr 4 33,34,43,44 . Flexible devices have received tremendous attention nowadays for their good foldability, high crack resistance, favorable compatibility, and potential application in portable and wearable devices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity decreased to the background level in 10 ms after the cease of the excitation source, indicating the suitability for high contrast imaging. The excellent performance of X-ray imaging could be attributed to the negligible self-absorption, high PLQE, light yield, and low detection limit of (C 38 H 34 P 2 )MnBr 4 33,34,43,44 . Flexible devices have received tremendous attention nowadays for their good foldability, high crack resistance, favorable compatibility, and potential application in portable and wearable devices.…”
Section: Resultsmentioning
confidence: 99%
“…The intensity decreased to the background level in 10 ms after the cease of the excitation source, indicating the suitability for high contrast imaging. The excellent performance of X-ray imaging could be attributed to the negligible self-absorption, high PLQE, light yield, and low detection limit of (C 38 H 34 P 2 )MnBr 4 33 , 34 , 43 , 44 .…”
Section: Resultsmentioning
confidence: 99%
“…These compounds may therefore not be suitable for applications that require photon counting and/or spectroscopic X-ray energy resolution capabilities, such as positron emission tomography and nuclear security. However, static X-ray imaging such as used in dental and physician practices would benefit from the low-cost nature of these materials and the high reported sensitivity, 119 which enables a low dose rate to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The first such study demonstrated that (bmpip) 2 SnBr 4 could function as an excellent X-ray scintillator ( Figure 5 A). 34 A very recent work found that square-pyramidal (PPN) 2 SbCl 5 also exhibits efficient X-ray scintillation, 119 and it is likely that many of these materials are radioluminescent. An open question is whether the long emission lifetimes ( Table 2 ) are problematic for X-ray detection.…”
Section: Properties Of Emissive 5s 2 0d Materialsmentioning
confidence: 99%
“…It is exciting that low‐toxic or non‐toxic elemental elements (such as Sn, Bi, Sb, Cu, and Ge) can replace lead to form lead‐free perovskites due to similar characteristics. [ 166–173 ] Lead‐free perovskite is a promising scintillator material because of its rich structural diversity, which is very suitable for various applications related to X‐ray detection and medical imaging. The diversified structure is closely related to the three vital ingredients (ionic radius, ion valence, and coordination type) of A, B, and X ions.…”
Section: Challenges and Outlookmentioning
confidence: 99%